Findings from the Myanmar Agriculture Policy Support Activity inform the Government of Myanmar’s response to the COVID-19 pandemic - CGIAR Research Program on Policies, Institutions, and Markets (2021)
As per a USAID factsheet published in 2022, the Myanmar Agriculture Policy Support Activity provided evidence to justify taking on debt from international finance institutions.